DEVELOPMENT THE VALIDATION OF INDONESIAN VERSION OF SF-36 QUESTIONNAIRE IN CANCER DISEASE - Dyah Ariani Perwitasari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
A Cancer patients need long term therapy in the treatment of their disease. One of the outcome of cancer treatment in patients of quality of life. Because of the limited instrument for measuring cancer patients’ quality of life in Indonesian version, thus this study is aimed to develop the validation of Indonesian version of Short Form-36 questionnaire in cancer patients. The observational study was carried out in this study. Data were collected from cancer patients in the Oncology Department of Sardjito Hospital, Yogyakarta, Indonesia, who were treated with cisplatin at the dosage of ≥ 50mg/m2 as monotherapy or in combinations. The validation process involved known-group validity, discriminant validity, convergent validity and factor analysis. About 203 subjects who were diagnosed with cancer were recruited in this study. Theknown-group validity test showed that there were no significant differences of SF-36 domains among different diagnosa. All of the questions met the criteria of convergent validity except for the questions number 26, 28, 30 and 32. Furthermore, the questions number 2 and 28 did not meet the criteria of discriminant validity. This study presents that many questions are needed to be reconstructed, due to the result of factor analysis which showed that those questions are loaded significantly with other domain’s questions. The development of Indonesian version of SF-36 scales in cancer disease is still less unstatisfactory. According to the result of this study, future study with new construction of questions in this version is still necessary.Key words: validation, SF-36, Indonesia, cancer